Cep126 is required for pericentriolar satellite localisation to the centrosome and for primary cilium formation. (9th July 2014) - Bonavita, Raffaella; Walas, Dawid; Brown, Anna K.; Luini, Alberto; Stephens, David J.; Colanzi, Antonino
<x xml:space="preserve">Abstract</x> Background Information The centrosome is the primary microtubule‐organising centre of animal cells and it has crucial roles in several fundamental cellular functions, including cell division, cell polarity, and intracellular transport. The mechanisms responsible for this are not completely understood. Results The poorly characterised protein CEP126 localises to the centrosome, pericentriolar satellites and the base of the primary cilium. Suppression of CEP126 expression results in dispersion of the pericentriolar satellites and disruption of the radial organisation of the microtubules, and induces disorganisation of the mitotic spindle. Moreover, CEP126 depletion or the transfection of a CEP126 truncation mutant in hTERT‐RPE‐1 and IMCD3 cells impairs the formation of the primary cilium. Conclusions We propose that CEP126 is a regulator of microtubule organisation at the centrosome that acts through modulation of the transport of pericentriolar satellites, and consequently, of the organisation of cell structure.